I am Kavi - Ponweera, Thushanthi (Holiday House, 2023)
"1998, Colombo. The Sri Lankan Civil War is raging, but everyday life must go on. At Kavi's school, her friends talk about the weekly Top 40, the Backstreet Boys, Shahrukh Khan, Leo & Kate... and who died--or didn't--in the latest bombing. But Kavi is afraid of something even scarier than war. She fears that if her friends discover her secret--that she is not who she is pretending to be--they'll stop talking to her. I want to be friends with these / happy, / fearless, / girls / who look like they / belong. So I could also be / happy, / fearless, / and maybe even / belong. Kavi's scholarship to her elite new school was supposed to be everything she ever wanted, but as she tries to find some semblance of normalcy in a country on fire, nothing is going according to plan. In an effort to fit in with her wealthy, glittering, and self-assured new classmates, Kavi begins telling lies, trading her old life--where she's a poor girl whose mother has chosen a new husband over her daughter--for a new one, where she's rich, loved, and wanted. But how long can you pretend to be someone else? This dazzling novel-in-verse comes from an astonishing new talent who lived through the civil war herself. Perfect for fans of Jamine Warga, Supriya Kelkar, and Rajani LaRocca, I Am Kavi centers a powerful South Asian voice, and stars an unforgettable heroine each and every one of us can relate to" --